The Strategy of Islamic Religious Education in Facing the Challenges of Multiculturalism in the Muslim Community of Suro Lembak Village, Kepahiang Regency - Tambunan, Zulham Luthfi; Astuti, Winda; Budiyono, Tri; Asiyah, Asiyah (AR-RASYID : Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the strategies of Islamic religious education in addressing the challenges of multiculturalism in Suro Lembak Village, Kepahiang Regency, focusing on how Islamic education fosters harmony among religious communities amidst cultural and religious diversity. Using a qualitative approach and library research methods, the data sources include books and journals related to Islamic education and multiculturalism. Descriptive analysis was employed to identify relationships between categories and derive relevant theories. The main findings reveal that Islamic religious education in Suro Lembak Village is implemented through formal and non-formal educational institutions, religious outreach (dakwah), and collaborative interfaith activities. Institutions such as madrasas and Quranic learning centers (TPA) teach Islamic values that promote tolerance and respect for differences, while dakwah emphasizes the importance of coexistence and interfaith dialogue to strengthen social harmony. Collaborative activities between religious groups have also successfully enhanced community solidarity. Despite the effectiveness of these strategies, the study notes several limitations, such as a lack of educators with expertise in multiculturalism, insufficient local policy support, and limited societal perceptions of diversity. The study suggests that teacher training, the development of contextually relevant teaching materials, and local government policy support are essential to strengthening multicultural education in the village.